2015
DOI: 10.1002/jmri.25052
|View full text |Cite
|
Sign up to set email alerts
|

On replacing the manual measurement of ACR phantom images performed by MRI technologists with an automated measurement approach

Abstract: The technologists' geometry measurements may be able to be replaced by automated measurement without compromising the weekly QC program required by the ACR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 12 publications
0
13
0
1
Order By: Relevance
“…There have been a number of publications of the ACR phantom test conducted on diagnostic MRI scanners (10)(11)(12)(13)(14) for diagnostic MRI QA/QC purpose, while the reports of ACR phantom test on dedicated MR-sim are still sparse (15). Our results showed that ACR phantom image acquired on a 1.5T dedicated MR-sim generally had sufficiently good image quality to pass all ACR recommended criteria, under a compromised flexible coil setting, thus fulfilled the basic requirements for clinical service.…”
Section: Discussionmentioning
confidence: 99%
“…There have been a number of publications of the ACR phantom test conducted on diagnostic MRI scanners (10)(11)(12)(13)(14) for diagnostic MRI QA/QC purpose, while the reports of ACR phantom test on dedicated MR-sim are still sparse (15). Our results showed that ACR phantom image acquired on a 1.5T dedicated MR-sim generally had sufficiently good image quality to pass all ACR recommended criteria, under a compromised flexible coil setting, thus fulfilled the basic requirements for clinical service.…”
Section: Discussionmentioning
confidence: 99%
“…International bodies such as the American College of Radiology (ACR) [19] and American Association of Physicists in Medicine (AAPM) [20] have given reference guidance on acceptance testing, commissioning and regular QA routines for clinical MRI scanners. The MRI QA test guidance from the ACR with its associated custom-designed phantom has become an important reference for routine MRI QA after acceptance into the ACR accreditation program [21][22][23][24][25][26]. The ACR protocol evaluates geometric accuracy, high-contrast spatial resolution, low-contrast object detectability, ghosting, image intensity uniformity, slice thickness and slice position accuracy [19].…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Multiple facilities have also reported automation of at least some of the ACR QC tests [11][12][13] but were either unable to automate the detection of the LC test patterns 13 or did not provide sufficient information to be able to reproduce their LC detection algorithms. 10,12,14 The work described by Fitzpatrick 9 did include a description of their algorithm and involved the detection of LC spokes by means of a two-step approach. This involved first segmenting the central LC pattern from the image using binarization of the central circular zone containing the LC spoke patterns followed by identification of the LC spoke patterns using cross-correlation of a set of disk templates along pre-determined radial lines within the segmented central zone containing the spoke patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Aside from the suite of algorithms developed by Bao et al that have been in use at our institution since 2007, other fully automated QC computer algorithms have been described . Multiple facilities have also reported automation of at least some of the ACR QC tests but were either unable to automate the detection of the LC test patterns or did not provide sufficient information to be able to reproduce their LC detection algorithms . The work described by Fitzpatrick did include a description of their algorithm and involved the detection of LC spokes by means of a two‐step approach.…”
Section: Introductionmentioning
confidence: 99%